Postembryonic development and male paedomorphosis in Osedax (Siboglinidae, Annelida) - Worsaae, Katrine; Rouan, Alice; Seaver, Elaine; Miyamoto, Norio; Tilic, Ekin (Frontiers in Neuroscience, 2024)
Most species of the bone-devouring marine annelid, Osedax, display distinct sexual dimorphism with macroscopic sedentary females rooted in bones and free-living microscopic dwarf males. The paedomorphic male resembles the non-feeding metatrochophore larva in size, presence of eight pairs of chaetae, and a head ciliation potentially representing a residual prototroch. The male development may thus uniquely reiterate and validate the theoretical heterochrony process “progenesis”, which suggests that an accelerated sexual maturation and early arrest of somatic growth can lead to a miniaturized and paedomorphic adult. In this study, we describe the postembryonic larval and juvenile organogenesis of Osedax japonicus to test for a potential synchronous arrest of somatic growth during male development. Five postembryonic stages could be distinguished, resembling day one to five in the larval development at 10°C: (0D) first cleavage of fertilized eggs (embryos undergo unequal spiral cleavage), (1D) pre-trochophore, with apical organ, (2D) early trochophore, + prototroch, brain, circumesophageal connectives and subesophageal commissure, (3D) trochophore, + telotroch, four ventral nerves, (4D) early metatrochophore, + protonephridia, dorsal and terminal sensory organs, (5D) metatrochophore, + two ventral paratrochs, mid-ventral nerve, posterior trunk commissure, two dorsal nerves; competent for metamorphosis. The larval development largely mirrors that of other lecithotrophic annelid larvae but does not show continuous chaetogenesis or full gut development. Additionally, O. japonicus larvae exhibit an unpaired, mid-dorsal, sensory organ. Female individuals shed their larval traits during metamorphosis and continue organogenesis (including circulatory system) and extensive growth for 2–3 weeks before developing oocytes. In contrast, males develop sperm within a day of metamorphosis and display a synchronous metamorphic arrest in neural and muscular development, retaining a large portion of larval features post metamorphosis. Our findings hereby substantiate male miniaturization in Osedax to be the outcome of an early and synchronous offset of somatic development, fitting the theoretical process “progenesis”. This may be the first compelling morpho-developmental exemplification of a progenetic origin of a microscopic body plan. The presented morphological staging system will further serve as a framework for future examination of molecular patterns and pathways determining Osedax development.